Dose Response Effects of Caffeine Ingestion on Salivary Immunoglobulin A Following High-Intensity Exercise - Gibson, Chloe (Auckland University of Technology, 2012)
Many athletes consume caffeine for its known ergogenic properties, with doses between 2-13 mg·kg-1 body mass (BM) being shown to enhance performance. While the range of ergogenic doses is large, caffeine has been reported to have no dose-response effect. In addition, large doses have been associated with negative side effects and have also been reported to have immunosuppressive effects, which have been attributed to increases in adrenaline. However, despite the prevalence of caffeine consumption in both athletic and non-athletic populations, and research showing the potential for caffeine to suppress some markers of immune function, little research has examined the effects of caffeine ingestion on immune function in response to exercise in humans. Therefore the aim of this thesis was to investigate the influence of several doses of caffeine (typically used in training and competition situations) on the saliva IgA response to prolonged high-intensity exercise. In a double-blind repeated-measures crossover design, 12 endurance-trained males ran for 70 min on a treadmill at 80% V̇O2peak, 60 min after ingesting 2, 4, 6 or 8 mg·kg-1 body mass (BM) of anhydrous caffeine or placebo (cornflour) (PLA, 2CAF, 4CAF, 6CAF or 8CAF). Un-stimulated whole saliva samples were obtained before supplementation, pre-exercise, mid-exercise, immediately post-exercise and 1 h post-exercise. Participants were habituated caffeine users and abstained from caffeine 60 h prior to trials. Trials were conducted 7 days apart at the same time of day. Saliva caffeine concentration was significantly higher in all caffeine trials than placebo at pre-exercise, mid-exercise, immediately post-exercise and 1 h post-exercise (P < 0.01). Saliva IgA concentration, secretion rate and saliva flow rate remained unchanged following placebo and caffeine trials. In contrast saliva α-amylase activity was higher in 6CAF, 4CAF and 2CAF trials when compared to PLA and 8CAF (P < 0.05). In conclusion, the findings of this thesis demonstrate that while ingesting caffeine doses of 2-8 mg·kg-1BM has neither a positive or negative affect on saliva IgA or flow rate, it does appear to increase α-amylase activity. While the biological significance of these findings in terms of caffeine’s potential to modify an individual’s susceptibility to infection following prolonged high-intensity exercise is unknown, it is suggested that athletes consume the lowest beneficial dose in order to avoid potential side effects observed with higher doses of caffeine.
Keywords: Saliva; IgA; Immune; Methylxanthine; Treadmill; Exercise